From Fear to Fascination: Using Virtual Reality to Ameliorate Pain and Anxiety in Pediatric Vascular Access Practices during Hemodialysis. A Review Article - Al Tarawneh, Fourat A.; M. Khamis, Moneeb (Journal of Neonatal Surgery, 2025)
Pediatric patients undergoing hemodialysis (HD) frequently suffer considerable pain and anxiety during vascular access steps. Non-pharmacological tools, such as virtual reality (VR), have been illuminated as promising approaches to alleviate these negative experiences. This review presents recent research advances in understanding the power of VR in lowering pain and anxiety in pediatric HD patients. VR, a technology that immerses users in simulated environments, has been shown to successfully distract patients from painful procedures, thereby reducing pain perception and anxiety levels. Research have revealed that VR can obviously decrease pain intensity, anxiety, and better patient satisfaction during vascular access procedures. By providing immersive experiences, VR can redirect attention away from the painful stimulus, modifying the physiological and psychological reactions correlated with pain and anxiety. As VR technology remains to advance, its integration into pediatric HD care has the eventual to pointedly meliorate the quality of life for young patients submit to these procedures.